Return On Aseet (ROA), Return On Equity (ROE), Debt Equity Ratio (DER), Firm Value (PER) - Delvi Kurnia Zebua (Indonesia Journal of Engineering and Education Technology (IJEET), 2023)
An abstract This study aims to: 1) Determine whether there are effects of ROA, ROE, and Capital Structure on Corporate Values both partially and simultaneously. 2) To find out how much influence ROA, ROE, and Capital Structure have on Corporate Values either partially or simultaneously. The analytical tool used is multiple linear regression, coefficient of determination, t test, and test f. Based on the results of the study show that there is a significant influence between Return On Aseet (ROA) on the value of the company. Return on Equity (ROE) there is significant effect on firm value. And Debt Equity Ratio (DER) has a significant effect on firm value. Whereas, simultaneously Return On Aseet (ROA), Return On Equity (ROE), Debt Equity Ratio (DER) there is a significant effect on firm value